Guidelines for the clinical management of Lynch syndrome (hereditary non-polyposis cancer). Issue 6 (27th February 2007) - Vasen, H F A; Möslein, G; Alonso, A; Bernstein, I; Bertario, L; Blanco, I; Burn, J; Capella, G; Engel, C; Frayling, I; Friedl, W; Hes, F J; et al.
Abstract : Lynch syndrome (hereditary non-polyposis colorectal cancer) is characterised by the development of colorectal cancer, endometrial cancer and various other cancers, and is caused by a mutation in one of the mismatch repair genes: MLH1, MSH2, MSH6 or PMS2 . The discovery of these genes, 15 years ago, has led to the identification of large numbers of affected families. In April 2006, a workshop was organised by a group of European experts in hereditary gastrointestinal cancer (the Mallorca-group), aiming to establish guidelines for the clinical management of Lynch syndrome. 21 experts from nine European countries participated in this workshop. Prior to the meeting, various participants prepared the key management issues of debate according to the latest publications. A systematic literature search using Pubmed and the Cochrane Database of Systematic Reviews reference lists of retrieved articles and manual searches of relevant articles was performed. During the workshop, all recommendations were discussed in detail. Because most of the studies that form the basis for the recommendations were descriptive and/or retrospective in nature, many of them were based on expert opinion. The guidelines described in this manuscript may be helpful for the appropriate management of families with Lynch syndrome. Prospective controlled studies should be undertaken to improve further the care of these families.